2010
DOI: 10.1111/j.1476-5829.2010.00222.x
|View full text |Cite
|
Sign up to set email alerts
|

Outcome and toxicity associated with a dose-intensified, maintenance-free CHOP-based chemotherapy protocol in canine lymphoma: 130 cases

Abstract: A dose-intensified/dose-dense chemotherapy protocol for canine lymphoma was designed and implemented at the Veterinary Hospital of the University of Pennsylvania. In this study, we describe the clinical characteristics, prognostic factors, efficacy and toxicity in 130 dogs treated with this protocol. The majority of the dogs had advanced stage disease (63.1% stage V) and sub-stage b (58.5%). The median time to progression (TTP) and lymphoma-specific survival were 219 and 323 days, respectively. These results a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
103
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(125 citation statements)
references
References 30 publications
18
103
1
1
Order By: Relevance
“…This result is similar to studies involving doseintensified chemotherapy that investigated canine lymphoma (Vaughan et al, 2007;Sorenmo et al, 2010). One recent report revealed that dogs that needed dose reductions and treatment delays after chemoradiotherapy had longer remission durations.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This result is similar to studies involving doseintensified chemotherapy that investigated canine lymphoma (Vaughan et al, 2007;Sorenmo et al, 2010). One recent report revealed that dogs that needed dose reductions and treatment delays after chemoradiotherapy had longer remission durations.…”
Section: Discussionsupporting
confidence: 90%
“…Based on our research, only three reports have indicated increased remission duration or survival time (ST) in dogs with lymphoma that required dose reduction and treatment delays after being treated with chemoradiotherapy or dose-intensified chemotherapy protocols (Vaughan et al, 2007;Sorenmo et al, 2010;Burton et al, 2013). However, no studies have investigated the effects of chemotherapyinduced neutropenia in dogs with lymphoma treated with conventional dosages of chemotherapy.…”
Section: Introductionmentioning
confidence: 86%
“…In canine lymphoma, dogs which developed grade 3 or 4 neutropenia following chemotherapy demonstrated improved outcomes, raising the possibility that more appropriate individual dosing was administered (Sorenmo et al . 2010; Vaughan et al . 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the fact that various multidrug chemotherapeutic protocols have been introduced, the median survival time in a recent study was approximately 12 months. 5 In general, the treatment of relapsed lymphoma results in a lower response rate and shorter remission duration compared with untreated lymphoma. [6][7][8] Early detection of tumor relapse and prompt therapy are a reasonable approach for managing recrudescent disease.…”
mentioning
confidence: 99%